Gap solitons in a dipolar Bose-Einstein condensate on a three-dimensional optical lattice - Muruganandam, P. [UNESP]; Adhikari, Sadhan Kumar [UNESP] (Iop Publishing Ltd, 2011)
We suggest and study the stable disc- and cigar-shaped gap solitons of a dipolar Bose-Einstein condensate of (52)Cr atoms localized in the lowest band gap by three optical-lattice (OL) potentials along orthogonal directions. The one-dimensional version of these solitons of experimental interest confined by an OL along the dipole moment direction and harmonic traps in transverse directions is also considered. Important dynamics of (i) the breathing oscillation of a gap soliton upon perturbation and (ii) the dragging of a gap soliton by a moving lattice along the axial z direction demonstrates the stability of gap solitons. A movie clip (available at stacks.iop.org/JPhysB/44/121001/mmedia) of the dragging of the three-dimensional gap soliton is included.